Tempeh’s Contribution to the Intake Vitamins B12, Folates and Essential Amino Acids - Castanheira, Isabel (2021)
Objectives: Tempeh is a plant-based fermented food consumed as an alternative source of protein. This study aims to compare the nutritional contents of some cooked tempeh and understand which way tempeh contributes to daily needs regarding its protein composition, B12 (cobalamins) and B9 (folates) vitamin contents.